2022
DOI: 10.1051/0004-6361/202142128
|View full text |Cite
|
Sign up to set email alerts
|

A multi-planetary system orbiting the early-M dwarf TOI-1238

Abstract: Context. The number of super-Earth and Earth-mass planet discoveries has increased significantly in the last two decades thanks to the Doppler radial velocity and planetary transit observing techniques. Either technique can detect planet candidates on its own, but the power of a combined photometric and spectroscopic analysis is unique for an insightful characterization of the planets, which in turn has repercussions for our understanding of the architecture of planetary systems and, therefore, their formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 114 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Introduction M dwarf stars have been a primary target in the search for exoplanets in recent years due to the large number of them in the galaxy. Their lower masses and luminosities compared to Sun-like stars make the planets in the so-called habitable zone (HZ) easier to detect with larger radial-velocity (RV) signal and shorter orbital period (Trifonov et al 2020;Sabotta et al 2021;González-Álvarez et al 2022). Current observations show that most planets orbiting around M-dwarfs have masses equivalent to a few Earth to Neptune masses (Trifonov et al 2020;González-Álvarez et al 2022), while Jupiter-mass planets are observed more frequently around Sun-like or more massive stars (Fischer & Valenti 2005;Reffert et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction M dwarf stars have been a primary target in the search for exoplanets in recent years due to the large number of them in the galaxy. Their lower masses and luminosities compared to Sun-like stars make the planets in the so-called habitable zone (HZ) easier to detect with larger radial-velocity (RV) signal and shorter orbital period (Trifonov et al 2020;Sabotta et al 2021;González-Álvarez et al 2022). Current observations show that most planets orbiting around M-dwarfs have masses equivalent to a few Earth to Neptune masses (Trifonov et al 2020;González-Álvarez et al 2022), while Jupiter-mass planets are observed more frequently around Sun-like or more massive stars (Fischer & Valenti 2005;Reffert et al 2015).…”
mentioning
confidence: 99%
“…Their lower masses and luminosities compared to Sun-like stars make the planets in the so-called habitable zone (HZ) easier to detect with larger radial-velocity (RV) signal and shorter orbital period (Trifonov et al 2020;Sabotta et al 2021;González-Álvarez et al 2022). Current observations show that most planets orbiting around M-dwarfs have masses equivalent to a few Earth to Neptune masses (Trifonov et al 2020;González-Álvarez et al 2022), while Jupiter-mass planets are observed more frequently around Sun-like or more massive stars (Fischer & Valenti 2005;Reffert et al 2015). GJ 1148, GJ 876 (Rivera et al 2010;Nelson et al 2016;Millholland et al 2018), and GJ 317 (Johnson et al 2007) are three unusual M-dwarf systems that have massive planets, whose formation is difficult to explain by the core-accretion theory of planet formation (Laughlin et al 2004;Morales et al 2019).…”
mentioning
confidence: 99%